دراسة مخبرية مقارنة لثلاثة معاجين قنيوية حاشية من حيث قدرة الختم الذروي (Latakia University Journal -Medical Sciences Series, 2016)
الهدف: مقارنة قدرة الختم الذروي لثلاثة معاجين قنيوية حاشية مختلفة في أسنان بشرية مقلوعة باستخدام طريقة تسرب الصباغ.المواد والطرق: تم تحضير 30 سناً بشرياً علوياً مقلوعاً أقصر من الذروة التشريحية بـ 1مم، ومن ثم قسمت عشوائياً إلى ثلاث مجموعات (n=10) وفقاً للمعجون الحاشي، حيث تم حشو المجموعة الأولى بأكسيد الزنك والأوجينول، والثانية بـ Adseal والثالثة بـ Apexit Plus ، بعد ذلك تمت تغطية الأسنان بطلاء الأظافر باستثناء 2-3مم من الذروة ومن ثم غمرت بصبغة أزرق الميتلين 2% لمدة 24 ساعة، وبعد ذلك تم غسل الأسنان وشطرها من أجل قياس التسرب الذروي داخل القناة.النتائـج:أظهرت نتائج التحليل الإحصائي أن التسرب المترافق مع أكسيد الزنك والأوجينول أقل بشكل ملحوظ بالمقارنة مع Adseal (P=0.004)، وApexit Plus(p=0.003)، مع عدم وجود فـــروق هامة في التسـرب بين AdsealوApexit Plus(P=0.99).الاستنتاجات: من خلال هذه الدراسة يمكن أن نستنتج أن أكسيد الزنك والأوجينول حقق ختماً جيداً للقناة بالمقارنة مع باقي المواد، في حين لم يكن هناك فرق في قدرة الختم بينAdsealوApexit Plus.Aim: to compare the apical sealing ability of three root canal sealers in human extracted teeth using dye penetration.Materials and Methods: thirty extracted human maxillary teeth were instrumented 1mm short of the anatomical apex and randomly assigned to three groups (n=10), according to the root canal sealer used for obturation. The teeth were divided into three experimental groups and obturated by cold lateral compaction of gutta-percha and one of the following sealers: group I, Zinc oxide and Eugenol sealer; group II, Adseal; group III, Apexit plus.The teeth were covered with nail varnish to within 2-3mm of the apical foramen and immersed in 2% methylene blue for 24 hours.After this period, the teeth were washed and cut longitudinally for apical leakage measurement inside the canal.Results: Statistical evaluation of the results showed no significant difference in the leakage between Adseal and Apexit plus (P =0.99). Leakage with ZOE was significantly lesser than Adseal (P=0.004) andApexit Plus (P=0.003).Conclusions:under the condition of this study, it can be concluded that ZOE presents lower apical leakage than Adseal and Apexit plus, and there was no significant difference in leakage between Adseal and Apexit plus.